2(3x+3)=3(2x+2)
multiply the first bracket by 2
(2)(3x)=6x
(2)(3)=6
multiply the second bracket by 3
(3)(2x)=6x
(3)(2)=6
6x+6=6x+6
move 6x to the left side
sign changes from +6x to -6x
6x-6x+6=6x-6x+6
0+6=0+6
6=6
Answer:
all real numbers
Answer:
x ≥ - 14
Step-by-step explanation:
![5x + 15 >= 3x - 13\\2x >= -28\\x >= -14](https://tex.z-dn.net/?f=5x%20%2B%2015%20%3E%3D%203x%20-%2013%5C%5C2x%20%3E%3D%20-28%5C%5Cx%20%3E%3D%20-14)
-2(a - 8) + 6a = 36
-2(a) + 2(8) + 6a = 36
-2a + 16 + 6a = 36
-2a + 6a + 16 = 36
4a + 16 = 36
- 16 - 16
4a = 20
4 4
a = 5
Answer: D is correct
Step-by-step explanation:
Answer:
let F=fee; R=hourly rate=1.2F ; N=number of hours
Total charge=F+NR
Total charge=F+N(1.2F)
$470=F+7(1.2F)
$470=F+8.4F
$470=9.4F
$50=F ANSWER 1: Her fee is $50
Step-by-step explanation: